The role of CT scanning in multidimensional phenotyping of COPD. - Bafadhel, M; Umar, I; Gupta, S; Raj, J; Vara, D; Entwisle, J; Pavord, I; Brightling, C; Siddiqui, S (2011)
BACKGROUND: COPD is a heterogeneous disease characterized by airflow obstruction and diagnosed by lung function. CT imaging is emerging as an important, noninvasive tool in phenotyping COPD. However, the use of CT imaging in defining the disease heterogeneity above lung function is not fully known. METHODS: Seventy-five patients with COPD (58 men, 17 women) were studied with CT imaging and with measures of airway inflammation. Airway physiology and health status were also determined. RESULTS: The presence of emphysema (EM), bronchiectasis (BE), and bronchial wall thickening (BWT) was found in 67%, 27%, and 27% of subjects, respectively. The presence of EM was associated with lower lung function (mean difference % FEV(1), -20%; 95% CI, -28 to -11; P < .001). There was no difference in airway inflammation, exacerbation frequency, or bacterial load in patients with EM alone or with BE and/or BWT ± EM. The diffusing capacity of the lung for carbon monoxide/alveolar volume ratio was the most sensitive and specific parameter in identifying EM (area under the receiver operator characteristic curve, 0.87; 95% CI, 0.79-0.96). Physiologic cluster analysis identified three clusters, two of which were EM predominant and the third characterized by a heterogeneous combination of EM and BE. CONCLUSIONS: The application of CT imaging can be useful as a tool in the multidimensional approach to phenotyping patients with COPD.